Cholecystoduodenostomy in Cats: indicate or not? - Corgozinho, Katia; Chaves de Jesus, Amanda; Carvalho dos Santos Cunha, Simone; Belchior Caloeiro, Cristiane; Motta, Marcella (Acta Scientiae Veterinariae, 2025)
Background: Cholecystoduodenostomy is a surgical procedure recommended for cats suffering from extrahepatic biliary tract obstruction (EHBTO) when biliary tract patency cannot be reestablished. However, this procedure is associated with high perioperative morbidity and mortality. Cats diagnosed with EHBTO are considered to be at high risk for anesthetic and surgical complications. This study reports the case of a cat with severe jaundice that underwent cholecystoduodenostomy and successfully recovered, sparking a discussion on whether this procedure should be recommended to treat EHBTO. Case: A 15-year-old neutered male domestic shorthair cat presented with progressive weight loss, abdominal distension, and jaundice. Serum biochemical analyses showed high alkaline phosphatase, alanine aminotransferase, γ-glutamyl trans-peptidase, and total bilirubin levels Abdominal ultrasonography revealed several abnormalities, such as enlargement of the common bile duct, distension of gallbladder, gallbladder wall thickening, hyperechoic hepatomegaly, large hepatic mass (5.5 x 8.7 cm in left medial lobe), and small irregular kidneys, while the results of serum biochemical analyses indicated liver dysfunction. The cat received supportive care treatment and was later subjected to hepatic mass removal surgery and cholecystoduodenostomy. Complications included postoperative hypotension and anemia, which were treated with a blood transfusion to correct the low packed cell volume (PCV). The cat’s hypotension improved after the transfusion, and there were no complications related to the biliary enteric anastomosis. Unfortunately, 3 months after the surgery, the cat fell ill, exhibiting symptoms of anemia and jaundice, and was therefore euthanized. Necropsy revealed pancreatic carcinoma. Discussion: The most common clinical signs of EHBTO in cats are vomiting, anorexia, lethargy, weakness, and weight loss. The cat of this report showed weight loss and abdominal distension. Vomiting and anorexia may not be present in cats with EHBTO. Abdominal ultrasonography is the primary imaging modality for biliary tract disease. The examination revealed an enlarged gallbladder with a thickened wall, moderately enlarged cystic duct, and dilated common bile duct, consistent with other reports in cats with EHBTO. The diagnosis of complete versus partial biliary obstruction is challenging, as animals with this condition may respond to medical treatment instead of requiring immediate surgery. In this case report, the decision was made to prioritize medical management before considering surgery, in an attempt to stabilize the clinical condition and deal with the hepatic mass. The animal was elderly, but its owner insisted on surgery despite its clinical condition and age. The survival outcome of a cat with EHBTO is influenced by various factors such as age, clinical condition, hepatic impairment, anesthesia, surgical expertise, and the medical expertise of the veterinary team. The cat of this report survived for 3 months after surgery. The veterinary team was initially hesitant to perform the surgery because the cat was in poor clinical condition and they doubted it would survive. However, the owner insisted on the operation. The question raised is: were the three months of survival worth it? For the owner, the 3 months of survival were worth it. When a veterinary team recommends surgery, it is important to consider the animal’s clinical condition, the owner’s perspective, and the surgical qualifications of the veterinary team. Keywords: jaundice, extrahepatic biliary obstruction, cholecystoduodenostomy, pancreatic carcinoma.